IMPLEMENTASI PEMBEKALAN PRANIKAH DALAM MEMBENTUK KELUARGA SAKINAH MAWADDAH WA RAHMAH - Mahmudin Mahmudin (Millah: Journal of Religious Studies, 2016)
One important factor in the preparation for marriage is a matter of debriefing before marriage for the bride and groom. This affects the readiness of the bride and groom to wade living together in a household. The program is expected to prospective brides can achieve a teaching / guidance in preparation to perfection and completeness of the meaning of life and living in a happy household. Household sakinah is the family life which is fostered by the marriage valid, capable of fulfilling the lives of spiritual and material worthy, capable of creating an atmosphere of affection (mawaddah warahmah) harmonious, and balanced and able to embed and implement the values of faith, devotion, and charitable pious and akhlakul karimah within the family according to the teachings of Islam. This is important because many divorces happened lately caused by misunderstanding interminable, unpreparedness in a foster home, and small habits that are not favored by the opposite sex.